The search for animal models for Lassa fever vaccine development - Lukashevich, Igor S (2013)
Lassa virus (LASV) is the most prevalent arenavirus in West Africa and is responsible for several hundred thousand infections and thousands of deaths annually. The sizeable disease burden, numerous imported cases of Lassa fever (LF) and the possibility that LASV can be used as an agent of biological warfare make a strong case for vaccine development. Currently there is no licensed LF vaccine and research and devlopment is hampered by the high cost of nonhuman primate animal models and by biocontainment requirements (BSL-4). In addition, a successful LF vaccine has to induce a strong cell-mediated cross-protective immunity against different LASV lineages. All of these challenges will be addressed in this review in the context of available and novel animal models recently described for evaluation of LF vaccine candidates.